SocioEconomic Challenges and Youth Deviance Among Immigrants - Patrick Agyare (SocioEconomic Challenges, 2025)

(untitled)
This paper examines how socioeconomic challenges contribute to youth deviance among immigrant communities in Norway. Despite Norway’s robust welfare structures – including anti-discrimination laws and access to education – many immigrant youth continue to face systemic barriers to meaningful inclusion. For these individuals, deviance often emerges as a response to exclusion, frustration, and blocked opportunities rather than an inherent behavioral tendency. Using qualitative content analysis of secondary sources, this paper explores how persistent inequalities in employment, housing, and education intersect with identity formation and social behavior. The findings indicate that when formal protections fail to ensure meaningful social integration, vulnerable youth may resort to deviant behaviors as a means of reclaiming agency or visibility. Effective strategies to address these challenges include stronger enforcement of anti-discrimination laws, equitable hiring practices, expanded educational access, stable housing initiatives, and employment-driven interventions tailored to vulnerable youth. These insights provide a grounded understanding of how deviance arises within institutional gaps and how existing systems can be adapted to foster inclusivity. While situated within the Norwegian context, these findings provide helpful suggestions for regions facing similar socioeconomic challenges. Future research should prioritize comparative analyses, longitudinal studies, and policy evaluations to assess the long-term impact of interventions aimed at reducing socioeconomic exclusion. Addressing these challenges through coordinated efforts is vital for providing stability and meaningful inclusion for vulnerable youth populations.